SAT0043 Inhibitory Potential of Specific Monoclonal Acpas in Two Mouse Subspecies Genetically Separated about One Million Years ago. (15th July 2016) - Grimm, C.; Marklein, B.; Rosenberger, K.; Konthur, Z.; Burmester, G.R.; Skriner, K.
Abstract : Background: Rheumatoid arthritis is believed to be induced by environmental, genetic and immunological factors. Monoclonal Anti-citrullinated protein autoantibodies ACPA target different proteins and their role in RA is still largely unknown Objectives: As a prerequisite to identify genetic factors involved in rheumatoid arthritis, we analyzed the susceptibility of PWD Mus musculus musculus subspecies, separated from Mus musculus domesticus about one million years ago to collagen antibody-induced arthritis (CAIA) and the role of ACPA antibodies in the CAIA model of arthritis. Methods: Collagen antibody-induced arthritis (CAIA) was induced by administration of collagen antibodies followed by lipopolysaccharide injection. Two genetically distinct mouse strains, representatives of the subspecies Mus musculus domesticus and Mus musculus musculus as well as their F1 hybrids, and consomis strains thereof were analyzed for the development of clinical and histological signs of arthritis upon CAIA treatment. ACPA antibodies were tested by adding it to the CAIA cocktail and their autoantigenic profile was generated using protein macroarrays previously described (Leidinger et al., 2009; Lin et al, 2007; Ludwig et al. 2008). Results: The wild-derived mouse strain PWD/Ph was highly susceptible to CAIA induced arthritis, whereas the classical laboratory strain C57BL/6J was resistant. Mice carrying chromosomes 5 or 12 from PWD on a B6 background display a B6-like phenotype in the CAIA model as well as the F1 hybrids (B6xPWD and PWDxB6) implicating the presence of dominant resistance modifiers in the C57BL/6J genetic background. The two mouse strains differ highly in their autoantigenic profile and the PWD strain show decrease of B-cells and IgA, IgG, IgM levels. Injecting specific monoclonal ACPAs reactive with the citrullintated H1 and H4 were able to block the CAIA induced arthritis. This inhibition can be explained in part by the inhibition of osteoclasts via a Toll 9 activation. DNAse treatment of ACPA immune complex blocks the the osteoclast inhibition in vitro in a dose dependent manner. Moreover TLR2 activation via P. gingivalis LPS and lipomannan treated animals show a 80% reduction of arthritis score compared to E. coli LPS in a C57BL/6J CAIA model. Anti-collagen specific antibodies are increased in both strains B6 and PWD when arthritis is induced.Rheumatoid factor RF was not detected in PWD or B6 mice before and after the CAIA-treatment nor in the LPS-treated control animals. Interestingly, the commercial CCP2 ELISA detected ACPA in some animals regardless of the treatment. Using the arginine and citrulline containing peptides as control shows that this response is directed to the arginine containing peptide and in most of the animals citrullination downregulates the antigenicity of the autoantibody targeted peptides. Conclusions: The Mus musculus musculus derived mouse strain PWD/Ph is highly susceptible to arthritis development in the CAIA model. TLR2 activation blocks CAIA and specific ACPAs are able to block Osteoclast activation via TLR9 activation and may be used as therapeutic antibodies in the future that protect from RA development. Disclosure of Interest: None declared